The Description of Hormonal Risk Factors of Breast Cancer Patients in RSUP Dr. Mohammad Hoesin Palembang - Hutahaean, Arekcsueng; Qodir, Nur; Fadilah, Mariatul; Umar, Mulawan; Roflin, Eddy (E-Jurnal Medika Udayana, 2021)
Breast cancer is a multifactorial disease. Most of the breast cancer risk factors are hormonal risk factors that associated with the length of exposure to estrogen hormone. This study is aimed to know the description of hormonal risk factors of breast cancer patients in RSUP Dr. Mohammad Hoesin Palembang. This study is a descriptive-observational study with cross-sectional design. Samples in this study are medical records of breast cancer patients in RSUP Dr. Mohammad Hoesin Palembang during January 2019 – August 2020 that meet the inclusion and exclusion criteria. In this study, 97 breast cancer patients were included as participant. Most of the participants had menarche at the age of 12 – 14 (72.2%), menopause at the age of 45 – 54 (38.1%), first pregnancy at the age of 20 – 29 (48.5%), parity  ? 3 times (46.4%), breastfed (76.3%), used hormonal contraception (71.1%), not used any menopausal hormone (96.9%), not consumed alcohol (100%) and normal nutritional status (56.7%).